Fuzzy Query Database Untuk Sistem Pendukung Keputusan Yang Cerdas - Poningsih, Poningsih; Jalalludin, Jalalludin (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The process of education and teaching is one of the acts of Tri Dharma College. The success of the learning process can not be separated from the role of a lecturer. Quality of faculty plays an important role in a college that wants to achieve the goal of teaching and learning processes that produce graduates (output) quality. Lecturer rated quality if it has the value of a good performance, which is reviewed from several aspects. This paper proposes an analysis based on the evaluation of faculty performance feedback using fuzzy query the database for intelligent decision support system. The value of diverse faculty performance, so as to the criteria of each lecturer is still ambiguous and still need to be clarified. Here will be determined three criteria of assessment of faculty performance is lacking, just and good. Of the three criteria are later obtained a recommendation to make a decision. Model rules obtained is the value of students and professors taken the maximum value, then rules obtained from students and professors taken minimum value, in order to obtain the value of the performance of lecturers as well as the criteria. Then the value of this performance, it can be used by institutions as advice on making a decision relating to a lecturer.